2021
DOI: 10.1371/journal.pone.0257234
|View full text |Cite
|
Sign up to set email alerts
|

Identification of high-risk COVID-19 patients using machine learning

Abstract: The current COVID-19 public health crisis, caused by SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2), has produced a devastating toll both in terms of human life loss and economic disruption. In this paper we present a machine-learning algorithm capable of identifying whether a given patient (actually infected or suspected to be infected) is more likely to survive than to die, or vice-versa. We train this algorithm with historical data, including medical history, demographic data, as well as COVID… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
63
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 46 publications
7
63
2
1
Order By: Relevance
“…Here we describe an innovative healthcare strategy to optimize the management system of COVID-19 patients while sparing resources for the care of patients with non-COVID-19-related conditions. Similar models have previously been proposed ( 18 , 19 ). MMCOs were designed to fill the gap of care delivery to COVID-19 patients with clinical features that are neither too mild to be managed by the GP in a home-based setting nor too severe to require ED admission or hospitalization.…”
Section: Discussionsupporting
confidence: 56%
“…Here we describe an innovative healthcare strategy to optimize the management system of COVID-19 patients while sparing resources for the care of patients with non-COVID-19-related conditions. Similar models have previously been proposed ( 18 , 19 ). MMCOs were designed to fill the gap of care delivery to COVID-19 patients with clinical features that are neither too mild to be managed by the GP in a home-based setting nor too severe to require ED admission or hospitalization.…”
Section: Discussionsupporting
confidence: 56%
“…A deep learning model achieved high sensitivity (90%) and high specificity (96%)in the detection of COVID-19 using chest CT with an area under the curve of 0.96 and an average time for each CT scan of 4,51 s [53] . In addition, an AI algorithm can identify patients who developed severe COVID-19 symptoms [55] , [56] . Quiroz-Juarez has presented a study for the early identification of high-risk patients among those exposed to the SARS-COV-2 virus, using a supervised artificial neural network [55] .…”
Section: Role Of the Aimentioning
confidence: 99%
“…In addition, an AI algorithm can identify patients who developed severe COVID-19 symptoms [55] , [56] . Quiroz-Juarez has presented a study for the early identification of high-risk patients among those exposed to the SARS-COV-2 virus, using a supervised artificial neural network [55] . The machine learning models were trained using comorbidities, patient demographic data, as well as recent COVID-19-related medical information.…”
Section: Role Of the Aimentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this situation, clustering or unsupervised machine learning approaches bring an opportunity to extract relevant information by identifying patterns, clusters, or profiles within large volumes of data. Although some machine learning or similar approaches have been implemented to investigate clinical symptoms, risk factors, and other parameters related to COVID-19 (Dixon et al 2021 ; Han et al 2020 ; Sudre et al 2021 ; Tong et al 2020 ; Kim et al 2020 ; Fu et al 2020 ; Alballa and Al-Turaiki 2021 ; Oshinubi et al 2021 , 2022 ; Quiroz-Juárez et al 2021 ; Zoabi et al 2021 ; Li et al 2020 ), to our knowledge, none has been formally reported from Costa Rican cases.…”
Section: Introductionmentioning
confidence: 99%